Repetita iuvant? A Note on the Concept of “repeated Exposure” in Aesthetics (Itinera, 2018)
Why do we make the aesthetic judgements and have the aesthetic preferences that we do? How and to what extent does repeated exposure to a certain aesthetic object influence our appreciation and taste for it? The present paper aims at reflecting on the role played by repetition in enhancing people's appreciation and attitudes towards an aesthetic stimulus (either a work of art or a natural object or event). Almost forty years ago the Polish-born psychologist Robert Zajonc famously championed the so-called "mere-exposure effect" hypothesis (Zajonc 1968), according to which repeated exposure of an individual to a stimulus is a sufficient condition for the enhancement of his/her attitude toward it. When applied to the aesthetic case, however, Zajonc's theory produces inconsistent evidence. Is repetition useful or, more precisely, is it true that "the more we repeat, the more we like"? Repetita iuvant?